Enhancing photovoltaic system maximum power point tracking with fuzzy logic-based perturb and observe method - Aziz Jafar, Muhammad Ihsan; Zakaria, Muhammad Iqbal; Dahlan, Nofri Yenita; Kamarudin, Muhammad Nizam; El Fezazi, Nabil (Institute of Advanced Engineering and Science, 2024)
Photovoltaic systems have emerged as a promising energy resource that caters to the future needs of society, owing to their renewable, inexhaustible, and cost-free nature. The power output of these systems relies on solar cell radiation and temperature. In order to mitigate the dependence on atmospheric conditions and enhance power tracking, a conventional approach has been improved by integrating various methods. To optimize the generation of electricity from solar systems, the maximum power point tracking (MPPT) technique is employed. To overcome limitations such as steady-state voltage oscillations and improve transient response, two traditional MPPT methods, namely fuzzy logic controller (FLC) and perturb and observe (P&O), have been modified. This research paper aims to simulate and validate the step size of the proposed modified P&O and FLC techniques within the MPPT algorithm using MATLAB/Simulink for efficient power tracking in photovoltaic systems.